PRWR: Evidence of Its Effectiveness in Teaching Academic Content-Area Reading Across English Proficiency - Lubis, Azhar Aziz; Sulistyo, Gunadi Harry (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This factorial quasi-experimental 22 study aimed to corroborate the effect of PRWR strategy compared to Translation and Reading Aloud on students’ academic content-area reading comprehension as observed from their English proficiency. The interaction between the strategy and English proficiency was also examined. Data were obtained from a reading comprehension test, a TOEFL PBT Equivalent test, and a questionnaire on students’ perception towards the PRWR strategy. Both the reading test and the questionnaire were expert validated and tried out, whereas the TOEFL PBT Equivalent test was conducted under the auspices of an English institute. 58 sophomore students at a state university in Malang, Indonesia, served as the subjects of the study. This turned out that first; students taught by the PRWR strategy have better reading comprehension than that of by Translation and Reading Aloud. Second, students with high English proficiency taught by the PRWR strategy have better reading comprehension than that of taught by Translation and Reading Aloud. Third, there was no interaction between reading strategy and English proficiency. All in all, the employment of the PRWR strategy was highly recommended in academic content-area reading comprehension.